2016
DOI: 10.1097/hjh.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of office systolic blood pressure according to both brachial and aortic measurements

Abstract: Type II (i.e. isolated high bSBP) and type III (i.e. isolated high aSBP) office SBP phenotypes were common and had intermediate level (between types I and IV) of arterial damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…39 The stronger correlations of TSI indices with aortic rather than brachial BP are important because aortic BP has been more strongly associated with indices of preclinical organ damage than brachial BP. 44,45 In hypertension, the vascular phenotype is characterized by reduced compliance, elasticity/distensibility, and increased stiffness. 46 With increased stiffness in large vessels, the pulsatile pressure/flow of the left ventricular ejection (which is normally transformed in a continuous flow) moves downstream to the small vessels of the arterial tree.…”
Section: Muscle Oxidative Capacity and Microvascular Reactivitymentioning
confidence: 99%
“…39 The stronger correlations of TSI indices with aortic rather than brachial BP are important because aortic BP has been more strongly associated with indices of preclinical organ damage than brachial BP. 44,45 In hypertension, the vascular phenotype is characterized by reduced compliance, elasticity/distensibility, and increased stiffness. 46 With increased stiffness in large vessels, the pulsatile pressure/flow of the left ventricular ejection (which is normally transformed in a continuous flow) moves downstream to the small vessels of the arterial tree.…”
Section: Muscle Oxidative Capacity and Microvascular Reactivitymentioning
confidence: 99%
“…Increased BP levels increase wall stress in vessels, promoting hypertrophy as an adaptive mechanism. Therefore, it is not surprising that many large adult studies, such as MESA (29), have demonstrated greater IMT at higher levels of BP whether measured in the clinic (30), at home (31), or by ambulatory BP monitoring (32). Longitudinal studies have demonstrated that baseline BP influences change in IMT (33,34), whereas improving morning BP peak leads to regression of IMT (35).…”
Section: Discussionmentioning
confidence: 99%
“…Пациенты распределялись в зависимости от АД на плечевой артерии и аортального давления. Пациенты, фенотип которых характеризовался повышением центрального АД, с нормальными или повышенными уровнями АД на плечевой артерии, имели более высокую вероятность уменьшения площади сечения сонных артерий даже после коррекции влияния других факторов по сравнению с лицами, имеющими нормальное центральное АД [16].…”
Section: клинические семинары §unclassified